Predictors of Preoperative Tinnitus in Unilateral Sporadic Vestibular Schwannoma - Naros, Georgios; Sandritter, Joey; Liebsch, Marina; Ofori, Alex; Rizk, Ahmed R.; Del Moro, Giulia; Ebner, Florian; Tatagiba, Marcos (Frontiers in Neurology, 2017)
Objective: Nearly two-thirds of patients with vestibular schwannoma (VS) are reporting a significantly impaired quality of life due to tinnitus. VS-associated tinnitus is attributed to an anatomical and physiological damage of the hearing nerve by displacing growth of the tumor. In contrast, the current pathophysiological concept of non-VS tinnitus hypothesizes a maladaptive neuroplasticity of the central nervous system to a (hidden) hearing impairment resulting in a subjective misperception. However, it is unclear whether this concept fits to VS-associated tinnitus. The present study aims to determine the clinical predictors of VS-associated tinnitus in order to ascertain the compatibility of both pathophysiological concepts. Methods: This retrospective study includes a group of 478 neurosurgical patients with unilateral sporadic VS evaluated preoperatively regarding the occurrence of ipsilateral tinnitus depending on different clinical factors, i.e. age, gender, tumor side, tumor size (T1-T4 according to the Hannover-Classification) and hearing impairment (Gardner-Robertson-Classification, GR1-5), using a binary logistic regression. Results: 61,8 % of patients complain about a preoperative tinnitus. The binary logistic regression analysis identified male gender [OR 1.90 (1.25–2.75); p = 0.002] and hearing impairment GR3 [OR 1.90 (1.08–3.35); p = 0.026] and GR4 [OR 8.21 (2.29–29.50); p = 0.001] as positive predictors. In contrast, patients with large T4 tumors [OR 0.33 (0.13–0.86); p = 0.024] and complete hearing loss GR5 [OR 0.36 (0.15–0.84); p = 0.017] were less likely to develop a tinnitus. Yet, 60 % of the patients with good clinical hearing (GR1) and 25% of patients with complete hearing loss (GR5) suffered from tinnitus. Conclusions: This data is good accordance with literature about non-VS tinnitus indicating hearing impairment as main risk factor. In contrast, complete hearing loss appears a negative predictor for tinnitus. For the first time, these findings indicate a non-linear relationship between hearing impairment and tinnitus in unilateral sporadic VS. Our results suggest a similar pathophysiology in VS-associated and non-VS tinnitus.